冷間強圧延したSUS316LN鋼のヘテロナノ組織とその形成過程 - 青柳, 吉輝; 小林, 秀平; 戸髙, 義一; 吉永, 直樹; 小林, 正和; 杉浦, 夏子; 三浦, 博己; 渡邊, 千尋 (鉄と鋼, 2019)
Evolution of heterogeneous nano-structure in heavily cold-rolled SUS316LN stainless steels was investigated in detail. Transmission electron microscopic observations from the transverse direction (TD) of the 92% rolled specimen revealed the formation of a typical hetero-nano structure composed of ultra-fine lamellae embedded with deformation twin domains. The twin domains had prolate ellipsoidal shape elongated parallel to TD. Two types of twin domains with different crystallographical orientations to matrices could be identified, i.e., i) // rolling direction (RD) and // TD or ii) // RD and // TD, although all the {111} twining planes of both twin domains were oriented nearly parallel to the rolling planes. The ultra-fine lamellae were elongated along direction and nearly parallel to RD. Deformation twins with a few nano-meter spacing were also frequently observed to develop in the lamellae. Evolution sequence of the hetero-nano structure during cold rolling was also investigated. At an early stage of rolling, deformation twins were gradually formed in the whole grains. Then, the regions fragmented grains by twins were further subdivided by a numerous number of shear bands inclined at about 20~45° from the RD, resulting in the formation of “eye-shaped” twin domains surrounded by shear bands and their crystallographical rotation. Cold rolling up to 50% caused a considerable increase in strength and decrease in ductility. While the strength was raised more with increasing reduction up to 92%, both the strength and ductility eventually slightly decreased by further rolling.